2017
DOI: 10.1016/j.atherosclerosis.2017.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Association of ectopic fat with abdominal aorto-illiac and coronary artery calcification in african ancestry men

Abstract: Background and aims There is strong evidence that fat accumulating in non-adipose sites, “ectopic fat”, is associated with cardiovascular disease (CVD), including vascular calcification. Most previous studies of this association have assessed only a single ectopic fat depot. Therefore, our aim was to assess the association of total, regional, and ectopic fat with abdominal aortoilliac calcification (AAC) and coronary artery calcification (CAC) in 798 African ancestry men. Methods Participants (mean age 62) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 51 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…Total muscle volume was slightly higher in current smokers compared to never smokers, though quantitatively the difference was consistent with the amount of excess IMAT in smokers. Our data suggest that assessing only lean or total muscle volume not only may lead to potentially missing important associations between muscle composition and risk factors such as smoking but also could underestimate the pathological impact of IMAT accumulation [16,18,19,46,47].…”
Section: Discussionmentioning
confidence: 93%
“…Total muscle volume was slightly higher in current smokers compared to never smokers, though quantitatively the difference was consistent with the amount of excess IMAT in smokers. Our data suggest that assessing only lean or total muscle volume not only may lead to potentially missing important associations between muscle composition and risk factors such as smoking but also could underestimate the pathological impact of IMAT accumulation [16,18,19,46,47].…”
Section: Discussionmentioning
confidence: 93%
“…The association of visceral fat with the severity of atherosclerosis in the aorta was assessed using ordinal logistic regression. We adjusted all models for height [ 31 34 ], which was used as a measure of the participant’s size. We adjusted the multivariate models for age, sex, smoking status, alcohol use, physical inactivity, hypertension, and diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, most measurements of VAT are performed by dual-energy X-ray absorptiometry, computed tomography, or magnetic resonance tomography. However, these imaging techniques are not appropriate for routine examinations because of their time expenditure, high cost, and radiation hazard [ 17 , 18 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological and pathophysiological studies have shown that the accumulation of visceral adipose tissue (VAT) is associated with a variety of CVD risk factors, including type 2 diabetes, hypertension, and metabolic syndrome [12][13][14][15][16]. Nowadays, imaging techniques, such as computed tomography, dual-energy X-ray absorptiometry, and magnetic resonance imaging, can accurately quantify the volume of VAT as well as the distribution of specific compartments [16][17][18][19]. However, these methods are not feasible in routine physical examinations because they are timeconsuming and expensive and have radiation risks.…”
Section: Introductionmentioning
confidence: 99%